2019
DOI: 10.1038/s41598-019-45566-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis whole genome sequencing provides insights into the Manila strain and drug-resistance mutations in the Philippines

Abstract: The Philippines has a high incidence of tuberculosis disease (TB), with an increasing prevalence of multidrug-resistant Mycobacterium tuberculosis (MDR-TB) strains making its control difficult. Although the M . tuberculosis “Manila” ancient lineage 1 strain-type is thought to be prevalent in the country, with evidence of export to others, little is known about the genetic diversity of circulating strains. By whole genome sequencing (WGS) 178 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 17 publications
(21 reference statements)
4
42
0
Order By: Relevance
“…Table 7 compares the distribution of lineage of MTB from our study with that from other studies [ 9 , 11 , 19 , 27 ]. L1 lineage was the most dominant in our and the Philippines study but in detail, the sublineage pattern was different [ 11 ]. L2 lineage was very prominent in a study from Yangon Region, Myanmar [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Table 7 compares the distribution of lineage of MTB from our study with that from other studies [ 9 , 11 , 19 , 27 ]. L1 lineage was the most dominant in our and the Philippines study but in detail, the sublineage pattern was different [ 11 ]. L2 lineage was very prominent in a study from Yangon Region, Myanmar [ 19 ].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have described the distribution of lineages of MTB and their associations with geographic and ethnic background of the TB patients in other parts of Southeast Asia [ 9 , 10 , 11 , 12 ]. A few genotyping studies in Myanmar were previously reported [ 7 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were three nsSNPs specific to L1.2.1, which is also known as EAI2 according to spoligotyping. It is a common sublineage of L1 but localized to Southeast Asia, where L1.2.1 was found in approximately 80% of all TB patients in the Philippines ( Phelan et al., 2019 ); L1.2.1.2 is common in Thailand and Myanmar ( Palittapongarnpim et al., 2018 ). The L1.2.1-specific SNPs were located in the coding sequences of narK2 (a proton/nitrate transporter) ( Giffin et al., 2012 ), rpfB and Rv1996 (universal stress protein) ( Table 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…Independent factors associated with loss to follow-up included patients' higher self-rating of the severity of vomiting as an adverse drug reaction and alcohol abuse [25]. It is known that most prevalent genotype of all MTB (37 cases) belonged to Manila type at 2014 [26] and recent whole genome sequencing clarified that the majority (80.3%) belonged to lineage 1 Manila clade with the minority belonging to lineages 2 and 4 [27]. It is difficult to conclude if new strains have been emerging because the locations of two studies are not the same.…”
Section: Infectious Disease Itself Is a Disastermentioning
confidence: 99%